Practical home-based physical activity programs for university students during the COVID-19 pandemic - Zhang, S.; Yu, L. (The Journal of Sports Medicine and Physical Fitness, 2021)
LETTERS TO THE EDITOR Since the first identified pneumonia cases of unknown origin COVID-19 has become a pandemic worldwide. At present, there is no vaccine specifically to prevent or treat the Coronavirus disease caused by the virus. Many countries and regions have advised people to reduce traveling and stay at home to avoid human-to-human transmission of the virus. As a result, most work, physical and recreational activities were suspended. In China, university students are required to study at home and take classes online. While social isolation is a Strategie measure to contain COVID-19, it may have unintended negative consequences, increasing the sedentary behavior and physical inactivity of university students. However, a number of researches suggested that physical activities such as moderate-intensity continuous training (MICT), resistance training (RT) and high-intensity interval training (HUT) have a significant effect on modulating the immune system.